Dynamic Effect of Corporate Investment Styles and Value of Quoted Manufacturing Firms in Nigeria - Gabriel Queen Ibim; Orukwowu Progress Austine (Journal of Management and Science, 2025)
This study examined the relationship between corporate investment policies and the market value of quoted manufacturing firms in Nigeria. Panel data of 17 quoted manufacturing firms was collected from the annual reports of the manufacturing firms from 2014-2023. Market of the quoted firms was modeled as the function of Long term investment measures as fixed assets to total assets, short term investment measures as current assets to total assets, portfolio investment measures as investment in equity to total assets and subsidiary investment measures as joint venture investment to total assets. Multiple regressions were formulated. Panel data methodology was employed while the fixed effects model was used as estimation technique at 5% level of significance. Fixed effects, random effects and pooled estimates were tested while the Hausman test was used to determine the best fit. Evidence from the findings shows that explained 60.2 percent of the systematic variation in the market value was explained by investment policy. The beta coefficient informed that short term portfolio investment, long term portfolio investment and long term investment have positive relationship with the stock prices of the quoted manufacturing firms while subsidiary investment have negative relationship with stock prices of the manufacturing firms. The probability coefficient of the variables informed us that short term portfolio investment and long term portfolio investment are statistically significant while long term and subsidiary investment are statistically not significant. from the findings, we conclude that corporate investment policies have significant relationship with value of the quoted manufacturing firms. The study recommends that managers of the manufacturing firms should devote adequate time in designing long term and portfolio investment policy that enhances firm’s shareholder value.